2021
DOI: 10.1302/1863-2548.15.210071
|View full text |Cite
|
Sign up to set email alerts
|

The increase in paediatric orthopaedic trauma injuries following the end of the curfew during the COVID-19 period

Abstract: Purpose The aim of this study was to compare the injury patterns of orthopaedic trauma patients in the paediatric age group who presented to our hospital during and after lifting the curfew due to the pandemic, with the patients of the same age group who presented to our institution during the same time period last year. Methods Patients, aged 0 years to 18 years, who presented to our clinic between 21 March 2020 and 31 May 2020 (during curfew) (Group A1, n = 111), between 01 June 2020 and 31 August 2020 (Grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Jin et al reported that the number of patients with allergic rhinitis and acute pharyngitis in the department of otolaryngology increased signi cantly from February to April 2020 compared to the previous three years 13 . Other studies with different inclusion times also showed an increase in pediatric consults 14,15 . From our research, no signi cant increase was observed in the number of patients during the COVID-19 period compared with the pre-COVID-19 period, but it is important to note that the number increased substantially during the post-COVID-19 period.…”
Section: Discussionmentioning
confidence: 76%
“…Jin et al reported that the number of patients with allergic rhinitis and acute pharyngitis in the department of otolaryngology increased signi cantly from February to April 2020 compared to the previous three years 13 . Other studies with different inclusion times also showed an increase in pediatric consults 14,15 . From our research, no signi cant increase was observed in the number of patients during the COVID-19 period compared with the pre-COVID-19 period, but it is important to note that the number increased substantially during the post-COVID-19 period.…”
Section: Discussionmentioning
confidence: 76%
“…Jin et al reported that the number of patients with allergic rhinitis and acute pharyngitis in the department of otolaryngology increased significantly from February to April 2020 compared to the previous 3 years [ 14 ]. Other studies with different inclusion times also showed an increase in pediatric consults [ 15 , 16 ]. From our research, no significant increase was observed in the number of patients during the COVID-19 period compared with the pre-COVID-19 period, but it is important to note that the number increased substantially during the post-COVID-19 period.…”
Section: Discussionmentioning
confidence: 78%
“…For example, a trend towards decreased injuries persisted for 12 months after the peak of the pandemic [ 5 ], and the number of paediatric orthopaedic surgery visits did not return to prepandemic levels in 2021 [ 6 ]. In contrast, a study by Kalem et al [ 35 ] found that after the first 3 months following the lockdown, the prevalence of outdoor traumas, high-energy traumas, the rate of patients treated with surgery, and the rate of admission to the emergency department were significantly higher than in the previous year. The authors assumed that children’s lower extremity muscle strength and neuromuscular control decreased after staying at home for a prolonged period.…”
Section: Resultsmentioning
confidence: 84%